How is the Spatial Linkage of Inclusive Economic Development in Java Island? - Suparta, I Wayan; Sari, Della Kurnia; Pratama, Ahmad Dhea (Universitas Bangka Belitung, 2023)
This study aims to analyze the spatial relationship of inclusive economic development between provinces in Java and how the open unemployment rate, inflation and average length of schooling affect the inclusive economic development index. The analysis was carried out using spatial concepts or not by using the value of the inclusive economic development index as the dependent variable and the open unemployment rate, inflation and average length of schooling as independent variables. The analytical methods and tools used in this study include Moran index analysis to see the spatial relationship of inclusive economic development between provinces, and panel data regression analysis to see the effect of the open unemployment rate, inflation and average length of schooling on the inclusive economic development index. . Based on the results of the study, it shows that there is no spatial linkage of inclusive economic development between provinces in Java. The open unemployment rate, inflation and the average length of schooling have a significant effect on the inclusive economic development index.